2017
DOI: 10.1038/s41598-017-18073-8
|View full text |Cite
|
Sign up to set email alerts
|

UV-B antagonises shade avoidance and increases levels of the flavonoid quercetin in coriander (Coriandrum sativum)

Abstract: Despite controlling a diverse array of regulatory processes in plants, UV-B wavelengths (280-315 nm)are attenuated by common greenhouse materials such as glass and polycarbonate and are therefore depleted in many commercial growing environments. In this study, we analysed the architecture, pigment accumulation and antioxidant capacity of coriander (Coriandrum sativum, also known as cilantro) plants grown with and without supplementary UV-B (1.5 µmol m −2 s −1 ). We demonstrate that UV-B limits stem elongation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 56 publications
(74 reference statements)
1
22
1
1
Order By: Relevance
“…To elucidate the causal dependency here, one would have to additionally compare fitness traits, e.g., investment in reproductive biomass or number of fertile seeds, and thus test whether fitness is also reduced or being maintained. In contrast to previous studies (Robson et al 2015, Fraser et al 2017, German individuals did not show any plant architecture change in response to UV radiation that might hint at a lack of necessity regarding strong photoprotection in their home range. However, both strategies might be a consequence of local selection due to ambient UV-B radiation intensities in the respective home range, as different UV response patterns of German and New Zealand individuals across the UV treatments clearly displayed differentiation of origins within species that is less likely to be affected by other local environmental factors.…”
Section: Genetic Differentiation and Local Adaptation In The Exotic Rcontrasting
confidence: 99%
See 1 more Smart Citation
“…To elucidate the causal dependency here, one would have to additionally compare fitness traits, e.g., investment in reproductive biomass or number of fertile seeds, and thus test whether fitness is also reduced or being maintained. In contrast to previous studies (Robson et al 2015, Fraser et al 2017, German individuals did not show any plant architecture change in response to UV radiation that might hint at a lack of necessity regarding strong photoprotection in their home range. However, both strategies might be a consequence of local selection due to ambient UV-B radiation intensities in the respective home range, as different UV response patterns of German and New Zealand individuals across the UV treatments clearly displayed differentiation of origins within species that is less likely to be affected by other local environmental factors.…”
Section: Genetic Differentiation and Local Adaptation In The Exotic Rcontrasting
confidence: 99%
“…, Fraser et al. ), German individuals did not show any plant architecture change in response to UV radiation that might hint at a lack of necessity regarding strong photoprotection in their home range. However, both strategies might be a consequence of local selection due to ambient UV‐B radiation intensities in the respective home range, as different UV response patterns of German and New Zealand individuals across the UV treatments clearly displayed differentiation of origins within species that is less likely to be affected by other local environmental factors.…”
Section: Discussionmentioning
confidence: 91%
“…Kaiserli (2018) reported that most cell-wall elongation genes induced by BRI1-EMS-SUPPRESSOR 1 (BES1) are negatively regulated by UV-B radiation [45]. Meanwhile, the biosynthesis and signaling of plant growth hormone auxin, a key regulator of stem elongation, was also suppressed in arabidopsis (Arabidopsis thaliana) and coriander (Coriandrum sativum) plants after UV-B radiation, thereby reducing plant stem elongation and promoting a compact phenotype [46]. In the present study, similar results such as reduced leaf area, increased leaf thickness, accumulation of leaf surface waxes, and reduced leaf internode length were observed, which are plant acclimation responses to supplemental UV-B radiation.…”
Section: Impacts Of Uv-b and Ppfd On Growth And Yieldmentioning
confidence: 99%
“…Ghasemzadeh et al (2016) reported that total phenolic and flavonoid content in green basil plants increased by 16% and 85%, respectively, after a 13 kJ•m −2 •h −1 post-harvest UV-B radiation for 4-10 h, but anthocyanin content was not measured [52]. It was also reported that upon supplemental UV-B radiation, the gene expression of phenylalanine ammonia lyase (PAL) and chalcone synthase (CHS), two key molecular markers for phenolic compounds biosynthesis increased significantly [46,53]. Noticeably, in the present study, the enhancement of flavonoids and phenolics by UV-B radiation was much greater than anthocyanin.…”
Section: Impacts Of Uv-b and Ppfd On Phytochemical Accumulation And Amentioning
confidence: 99%
“…The Apiaceae family contains additional economically important plants, such as ajwain, angelica, anise, asafoetida, caraway and chervil (Feng et al, ; Que et al, ; Shelef, ). In recent years, a large number of studies have been reported on the phenotype, physiology, stress resistance, gene expression and metabolite identification of coriander (Abbassi et al, ; AlQuraidi et al, ; Choudhary et al, ; Divya et al, ; Fraser et al, ; Gholizadeh et al, ; Verma et al, ). However, among all the Apiaceae species, only the carrot genome has been sequenced until now (Iorizzo et al, ).…”
Section: Introductionmentioning
confidence: 99%